E-COMMERCE AND CHANGES IN CONSUMER BEHAVIOUR IN THE ECONOMY 5.0 ERA - Sigit Sugiardi; Apriyanto; Kevin Hermanto Tupamahu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The rapid development of E-Commerce in the Economy 5.0 era has triggered drastic changes in consumer behaviour. Modern consumers demand a fast, convenient and personalised shopping experience, supported by advanced technologies such as artificial intelligence (AI) and big data. Consumers are now more informed and active in the purchasing process, often conducting in-depth research and taking advantage of online reviews before deciding to buy a product. They also expect a seamless integration between online and offline shopping experiences. These changes require businesses to adapt and innovate in order to meet ever-increasing consumer expectations. An omnichannel strategy is important in ensuring consistency and quality of the customer experience. Businesses also need to continue to take advantage of the latest technology to provide relevant and secure services. Ultimately, these changes are forcing businesses to focus more on customer needs and wants, driving the creation of added value that can increase customer loyalty and satisfaction. Adaptability and innovation are key for businesses to remain competitive in the dynamic Economy 5.0 era.